Tree Association with Pometia and its Structure in Logging Concession of South Papua Forest - Agustinus Murdjoko; Djoko Marsono; Ronggo Sadono; Suwarno Hadisusanto (Institut Pertanian Bogor (IPB University), 2016)
Part of forests in Papua is still as logging concession. Pometia is one of target species, but there is still a lack of information regarding the ecological condition of this species. Thus, the objectives of this research were to describe what tree species (small and large individuals) associated with Pometia, how logging and soil properties influence the association and to analyze the structure of Pometia in term of diameter distribution. Canonical correspondence analysis (CCA) was applied to describe the association and its relationship with environmental factors (soil and litterfall). The results showed that association of small and large individuals of trees with both Pometia showed a different pattern in which the small individuals had a positive association and had certain tree species as a community. This association resulted from logging activity leading to the change in ecological conditions. Conversely, the association between large tree species with Pometia acuminata Radlk. and Pometia pinnata J. R. Forst. & G.Forst. showed negative pattern and tree species correlated with both Pometia were different. Of environmental factors, only C content of litterfall had a positive correlation with large Pometia acuminata and its community. Furthermore, the small individuals of Pometia were dynamic as a response to logging in which a number of the small individuals of Pometia tended to increase after logging.